EKTRAKSI SILIKON DIOKSIDA DARI DAUN BAMBU - Halimah Sa'diyah; Salamet Nurhimawan; Sigit Ahmad Fatoni; Irmansyah Irmansyah; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Silika extract has got from bamboo leaf by leaching with HCl 7% p.a. After bamboo leaf was burned, the charcoal was heated in the furnace with annealing rates of 0.9 and 1 °C/minute. The first temperature was room temperature, then increased to 400 °C with 2 hours arrested time. And last increased to 950 °C with 1 hour arrested time. The resulting ash was leached with HCl 7% p.a and its pH was neutralisted by aquabides. Then, the neutral ash was heated in furnace at 1000 °C. The result of EDX analysis showed that silica samples have purity levels of 84.53% to 99.99%. FTIR result showed that silica samples have absorption bands at wave numbers of 1071 cm-1, 1060 cm-1 and 798 cm-1 which indicate the asymetric stretching vibration of Si-O from siloxane group. Keywords: silica, bamboo leaves, purity level, function group.